Women and business in a knowledge-based society: integrated services network to sustain women's employment - Viapiana C. (Women status in the Mediterranean: their rights and sustainable development, 2009)
Progetto Pubblicità of Bari, as implementing agency, has involved some of the most important local partners to promote this initiative in the district area, within a European perspective, in the field of communication and awareness-raising. A new model has been elaborated that integrates traditional consulting services, creativeness, planning, with all forms of communication. The agency intends to satisfy local needs to improve services and policies supporting women's employment. Progetto pubblicità tends to focus its strategic planning on the construction of a local network through the integration and enhancement of women's work, the promotion of their careers and their greater access to employment.
International Meeting on Women Status in the Mediterranean: their Rights and Sustainable Development, 2008/06/16-17, Bari (Italy)